2011
DOI: 10.1080/00051144.2011.11828404
|View full text |Cite
|
Sign up to set email alerts
|

ECG based prediction of Atrial Fibrillation using Support Vector Classifier

Abstract: Original scientific paperIn patients undergoing Coronary Artery Bypass Grafting (CABG) surgery postoperative atrial fibrillation (AF) occurs with prevalence of up to 40%. The highest incidence is between the second and third day after the operation. Following cardiac surgery AF causes various complications, hemodynamic instability, and can cause heart attack, cerebral and other thromboemolisms. AF increases morbidity, duration and expense of medical treatment. This study aims to identify patients at high risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Traditional techniques for AF prediction combine discrete features extracted from ECGs and machine learning classifiers 12 , 13 . Promising features for the prediction of AF, such as P wave duration, RR interval duration, and PQ segment level, have been considered in the literature 14 . However, this kind of approaches takes into account only little information from the ECG and require a time-consuming phase to extract and select handcrafted features 15 , also prone to errors.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional techniques for AF prediction combine discrete features extracted from ECGs and machine learning classifiers 12 , 13 . Promising features for the prediction of AF, such as P wave duration, RR interval duration, and PQ segment level, have been considered in the literature 14 . However, this kind of approaches takes into account only little information from the ECG and require a time-consuming phase to extract and select handcrafted features 15 , also prone to errors.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study [21,22], we claimed that changes in the PQ segment level (defined as elevation / depression of the segment level between P wave end and Q wave onset) and the falling P wave slope are related to premature atrial repolarization, APD shortening and loss of AP plateau, and this is often found in patients prone to atrial fibrillation [21,22]. These hypotheses were tested again with the 2D cardiac model of this study and the results (Fig.8.…”
Section: Discussionmentioning
confidence: 98%